Larval body patterning and apical organs are conserved in animal evolution - Marlow, Heather; Larsson, Tomas; Arendt, Detlev (BMC biology, 2014)
Planktonic ciliated larvae are characteristic for the life cycle of marine invertebrates. Their most prominent feature is the apical organ harboring sensory cells and neurons of largely undetermined function. An elucidation of the relationships between various forms of primary larvae and apical organs is key to understanding the evolution of animal life cycles. These relationships have remained enigmatic due to the scarcity of comparative molecular data.